The Relationship Between ESG Scores and Firm Value of Listed Companies in the Stock Exchange of Thailand and the Indonesia Stock Exchange - Kobkanjanapued, Yodsawinkan (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
This study aims to examine the relationship between Environmental, Social, and Governance (ESG) performance scores and firm value (Tobin’s Q) and compare this relationship between listed companies on the Stock Exchange of Thailand (SET) and the Indonesia Stock Exchange (IDX). Adopting a quantitative research approach, the study utilizes a sample of 1,129 firm-year observations from both exchanges. Data analysis was conducted using descriptive statistics, correlation analysis, and panel data regression with a Fixed Effects Model. The findings reveal that 1) ESG scores have a statistically significant positive relationship with firm value. This reflects that sustainability performance effectively creates value added and enhances stakeholder confidence. 2) There is no statistically significant difference in the relationship between ESG scores and firm value between Thailand and Indonesia. This indicates that capital market mechanisms in both countries respond to ESG factors with a consistent direction and magnitude. Research Findings and Implications: The results suggest that capital markets in ASEAN emerging economies are moving toward a unified integration of sustainability valuation standards. These findings are beneficial for executives in establishing ESG as a core corporate strategy to enhance firm value. Furthermore, they provide a framework for regulators to collaborate on defining regional disclosure standards to effectively attract international sustainable investment.